Refuse of the city: rethinking waste management in Brussels - Andrea Bortolotti (Brussels Studies, 2021)
The image and perception of a city are intrinsically tied to its cleanliness. Everywhere in the world, working-class neighbourhoods with rubbish piling up in the streets are subject to stigma and devaluation. This is the case in Cureghem, a multi-ethnic district of Brussels, Belgium, where the lack of cleanliness and maintenance of the public space are among the main concerns and complaints expressed by inhabitants. This paper examines the rubbish collection service in Brussels, focusing in particular on a shopping street in Cureghem with an abundance of ethnic restaurants, bars and greengrocers, where rubbish accumulation is largely attributed to the vibrant commercial activity. Based on fieldwork, interviews and workshops with local stakeholders conducted in the framework of a transdisciplinary research project, it aims to shed light on the rubbish problem in Cureghem and the proposals which emerge in the search for a solution.